A baboon walking on a treadmill: the use of positive reinforcement techniques to study bipedal walking in non-human primates - François Druelle; Pablo Molina-Vila (Revue de Primatologie)
To date, the use of positive reinforcement techniques to study locomotion in non-human primates remains poorly developed. However, using cooperative animals that can freely move in experimental setup allows us to collect valuable and relevant data and makes these repeatable and comparable between species. Based on the current knowledge and our experience, we present an experimental approach that aims at reaching the standards of the study of human movement in a non-human primate, the olive baboon, Papio anubis, thanks to the use of positive reinforcement techniques. This report documents the training protocol that we set up at the Primatology station of the CNRS (France). We further elaborate on the importance of conducting such experiments for a better and finer understanding of the bipedal behaviour in non-human primates. Experimental studies including cooperative animals that can freely move are likely to represent valuable experimental tools to fill important gaps of knowledge in the study of locomotion in general, and in the study of the acquisition of habitual bipedal walking in hominins.